ADVANTAGES AND DISADVANTAGES OF USING CLOTHING BRANDS - Singh, Swarnlata; Kaur, Veerpal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Brands are the medium between consumers and producers which helps in creating a balance. Excess of anything will always harm us. Along with this, we should work on ourselves. There is a need to understand the psychology of brands at such times, when we are looking for the advantages and disadvantages of brands. By keeping these advantages and disadvantages in mind, both consumers and companies can make better decisions. The study of brand psychology is that which focuses on understanding what kind of feelings, thoughts, beliefs, behavior and frequency of purchase consumers develop towards the brand. It includes many aspects. Such as emotional attachment (with the brand), social influence, brand identity, previous and new experiences and decision making process etc. By understanding this psychology, companies make their marketing strategies more effective. Everything depends on the consumer, so it is necessary to know brand psychology.